Does caffeine affect the response of blood lactate to desensitization activities in young swimmers? - Afshin Rahbarghazi; Marefat Siahkouhian; Lotfali Bolboli (Institue of Medicinal Plants, ACECR, 2020)
Background: Caffeine is considered as one of the most nutritional supplements and the most consuming stimulant among athletes. Objective: The purpose of this study was to investigate the effect of caffeine on blood lactate response following exhaustive activities in the chest and chest bite of young male swimmers. Methods: This quasi-experimental study was performed and 16 male young swimmers were randomly divided into two groups. At first, swimmers without caffeine took part in a 100-meter long chest and back chest for the purpose of initial recording. Then, after seven more refreshments, taking caffeine was recorded. Blood lactate samples were taken in three stages of the basal state, after the supplementation period and immediately after exercise. Data were analyzed using repeated measure ANOVA, Bonferroni and independent correlation T-test. Results: The results of repeated analysis of variance showed that the consumption of caffeine had a significant effect on blood lactate response after exhaustive activities compared with the control group (P < 0.001) and also improved the record performance of swimmers (P < 0.001). Conclusion: The results showed that consumption of caffeine in groups had a significant effect on blood lactate and swimmerschr('39') performance, but there was no significant difference between breast and back chest groups.